Utilization of a two-material decomposition from a single-source, dual-energy CT in acute traumatic vertebral fractures - Tivnan, Patrick; Kaliaev, Artem; Anderson, Stephan W.; LeBedis, Christina A.; Li, Baojun; Andreu-Arasa, V. Carlota (Frontiers in Radiology, 2023)
Purpose. Utilizing two material decomposition to quantify signs of bone marrow edema on dual-energy CT (DECT) scanner at cervical, thoracic and lumbar spine acute fractures in correlation with STIR hyperintensity on MR, in comparison to normal bone marrow. Materials and Methods. This retrospective IRB approved study gathered patients over 18 years old scanned on DECT scanner who had acute cervical, thoracic or lumbar spinal fractures. Those that had a spinal MR done with bone marrow STIR hyperintensity within three weeks of the DECT were included. Water (calcium) and fat (calcium) region of interest measurements of the water and fat density (mg/cm3) of the bone marrow were obtained at a normal anatomic equivalent site and the fracture site where STIR was noted on MR. Statistical analysis was performed using the paired t-test and Wilcoxon signed rank test (p > 0.05). Results. 20 patients met inclusion criteria (males n=17 males, females n=3). A total of 32 fractures were analyzed: 19 cervical and 13 thoracolumbar. There were statistically significant differences in the water (43 ± 24 mg/cm3) and fat (36 ± 31 mg/cm3) density (mg/cm3) at the acute thoracic and lumbar spine fractures in correlation with edema on STIR images (both paired t-test <0.001, both Wilcoxon signed ranked test p<0.01). There were no significant differences in the water (-10 ± 46 mg/cm3) or fat (+7 ± 50 mg/cm3) density (mg/cm3) with cervical spine fractures. Conclusion. DECT two material decomposition using water (calcium) and fat (calcium) analyses have the ability to quantify bone marrow edema at the acute fracture site in the thoracic and lumbar spine.